KONSEP MULTIKULTURAL PERSPEKTIF KH. IMAM ZARKASYI - Dakir Dakir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2017)
The purpose of this study is to identify and analyze the thoughts of Islamic multicultural education proposed by KH Imam Zarkasyi in or- der to find the rationale and the construction of thoughts as well as the contribution to Islamic civilization in Indonesia through historical-philo- sophical approach. The results of the study showed that the rationale of Islamic multicultural education proposed by KH. Imam Zarkasyi referred to the principle of the unity of man or unity of creation and the unity of knowledge, as a reflection of the nature of one God conception. The in- terpretation of the concept created internalization approach regarding the spiritual reason in which every human work stepped on the objective value and implications on the orientation of God as the minimum ratio- nality to release the negative spirit, dichotomy, liberalization of science, socio-cultural, fanatics of tribes/nation/race/ethnic group/culture, or the overall types of the local/national/international students’ souls through the integration of the value in terms of diverse knowledge and socio- cultural values based on Islamic teaching values, cultural philosophy of Indonesian identities, socio-cultural diversity of local/national/interna- tional students and the integration of Education Center in terms of social structure equal to the form of communal religious, had formed a balance of value function and changes of attitudes, intellects and the strength of local/national/international Moslems as the power of socio-religious Mos- lems in Indonesia in order to foster peace throughout the world. The above findings showed the integrated points of view on religion, metaphysics and reason that determined the consciousness of human morality, not as the guidance of thoughts and ratio.